IMPROVING THE PREVENTION OF OFFENSES AGAINST MORALITY (USING THE EXAMPLE OF PROSTITUTION AND MAINTAINING A BROTHEL) - Khudayberdiev Abdurashid Abdirasulovich; Ergashov Olimkhon Alisherovich (The Conference Hub, 2025)
Certain measures have been implemented to prevent and combat crimes related to maintaining brothels or pimping. First and foremost, during this period, a normative-legal framework was established to eliminate these crimes. On September 22, 1994, Article 131 of the Criminal Code of the Republic of Uzbekistan, titled “Maintaining a Brothel or Pimping,” established criminal liability to combat such acts. As a result of criminal-legal reforms, the norms of criminal legislation concerning liability for organizing or maintaining a brothel, or pimping with mercenary or other base motives, have been further improved.